Prevalence and predictors of psychological problems among principal caregivers of children with cerebral palsy in Galle, Sri Lanka - C J Wijesinghe; C G Hewage; P Fonseka (College of Community Physicians of Sri Lanka, 2014)
Background Caregivers of children with disabilities are easy victims of psychological ill-health. Assessment of psychological problems and identification of factors predicting such outcomes are vital in identifying high-risk caregivers, to prevent them from becoming second order patients. Aim To describe the prevalence and predictors of psychological problems among principal caregivers of children with Cerebral Palsy (CP) in the Galle district Methods The study included 375 caregivers of children with CP, attending Teaching Hospital, Karapitiya, Galle. Prevalence of psychological problems of caregivers was assessed using the General Health Questionnaire (GHQ). Level of caregiver burden was assessed using Caregiver Difficulties Scale, developed and validated by the authors. An interviewer administered questionnaire was used to collect data on other study variables. Predictors of psychological problems in caregivers were determined using logistic regression analysis. Results Fifty six percent (95% Confidence Interval = 51.0% 61.0%) of caregivers had GHQ scores above the cut off threshold for psychological disorders. The strongest predictor for presence of psychological problems was high level of caregiver burden {Odds Ratio (OR)=19.99(5.54-72.13),p<0.001}. Lower educational level of the caregiver {OR=3.65(1.78-7.48),p<0.001} and younger age of the child {OR=3.97(1.88- 8.37),p<0.001} were also predictive of psychological problems. Other predictors included the use of more treatment types {OR=2.04(1.13-3.67),p<0.05} and not seeking support for care giving {OR=1.82(1.00-3.31),p<0.05}. Conclusions Caregivers of children with CPshow a high prevalence of psychological problems. There are a number of factors predictive of caregiver psychological problems, particularly the level of caregiver burden, which need to be considered when developing long term care plans for children with CP. DOI: http://dx.doi.org/10.4038/jccpsl.v19i1.7621 Journal of the College of Community Physicians of Sri Lanka Vol.19(1) December 2013 8-17